Separate Turbo Code and Single Turbo Code Adaptive OFDM Transmissions - Burr Alister; Ye Lei (EURASIP Journal on Wireless Communications and Networking, 2009)
Abstract This paper discusses the application of adaptive modulation and adaptive rate turbo coding to orthogonal frequency-division multiplexing (OFDM), to increase throughput on the time and frequency selective channel. The adaptive turbo code scheme is based on a subband adaptive method, and compares two adaptive systems: a conventional approach where a separate turbo code is used for each subband, and a single turbo code adaptive system which uses a single turbo code over all subbands. Five modulation schemes (BPSK, QPSK, 8AMPM, 16QAM, and 64QAM) are employed and turbo code rates considered are and . The performances of both systems with high ( ) and low ( ) BER targets are compared. Simulation results for throughput and BER show that the single turbo code adaptive system provides a significant improvement.